Hubungan Pembagian Nurse Shift dan Overtime Working dengan Produktivitas Kinerja Perawat di Ruang Rawat Inap Rumah Sakit Labuang Baji Makassar - Mokodompit, Kurniawan; Agustini, Tutik; Siokal, Brajakson (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Labor productivity can be affected by various factors such as shift work and overtime working , where the work shift is a method of division of time that has different working hours while overtime work or overtime working is a type of work that is done outside of normal working hours .This study aims to determine the relationship between the division of Nurse Shift and Overtime Working with Performance Productivity in the Inpatient Room of LabuangBaji Hospital in Makassar.This research is a type of Cross Sectional Study, this research was conducted by direct observation by researchers, the determination of the sample was carried out by total sampling technique with a sample size of 35 respondents who met the inclusion criteria, the relationship test was performed with the Chi-Square test with a significance level Î± <0.05.The results showed that there was no relationship between nurse shift with performance productivity using the Chi- Square test obtained Ï = 0, 203 and there was no relationship between overtime working with performance productivity using the chi square test obtained Ï = 0.603 . It is recommended to hospital agencies to routinely provide motivation to improve morale and work ethic so as to cause high dedication , the management also routinely conducts surveillance of nurse productivity .